THE EFFECT OF SELF-EFFICACY AND SELF-ESTEEM ON STUDENTS ACADEMIC PERFORMANCE IN MANADO - Tumboimbela, Rifio Sovian; Tumbuan, Willem J. F. A.; Pandowo, Merinda H.C (Universitas Sam Ratulangi, 2019)
Abstract: Good academic development not only affects study results but also affect a person’s future. Some of the factors that affect academic development including self-efficacy and self-esteem. This study aims to analyze the existence of the influence of self-efficacy and self-esteem on student academic performance in Manado. This research uses quantitative methods. The data of this study were obtained from questionnaire, the respondents are IBA student batch 2015 Faculty Economics and Business University of Sam-Ratulangi with 63 samples. The statistical analysis used was multiple regression analysis using the SPSS 25. The findings indicates that the variables of self-efficacy and self-esteem simultaneously has significant effect on student academic performance of IBA students with F test significance 0.035 < 0.05. The variables of self-efficacy and self-esteem have partial significant effect on student academic performance with T test of self-efficacy significance 0.038 < 0.05, self-esteem 0.044 < 0.5. The most dominant variable affecting student academic performance is self-efficacy. Based on the results the researcher concluded that self-efficacy and self-esteem has a significant and positive effect on student academic performance. It’s recommended for IBA students reconsidering of this result to increase the self-efficacy and to improve self-esteem so that academic performance can increase.Keywords: student academic performance, self-efficacy, self-esteem.